A Proposal of a Dynamic Routing Multicast Protocol for Visible Light Communication Networks - Sales, Frederico O.; Silva, Edelberto Franco; Vieira, Alex B.; Vieira, Marcos A. M.; Vieira, Luiz F. M. (Anais do Workshop on Security, Privacy and Reliability on Wireless Sensing Networks (WSENSING), 2021)
Wireless networks have grown since the 2000s. Compelling to rethink the way to enrich the possibilities to outflow the network traffic and its coverage. Current Visible Light Communication (VLC) systems focus mainly on wireless solutions. Converting multicast to unicast. Because of it, we propose an evolution of unicast and multi-hop wireless Optical Wireless Communication (OWC) supporting multicast communication in VLC environments, called MCAST-VLC. MCAST-VLC is a cross-layer dynamic routing protocol for VLC scenery, considering some particular characteristics of this area. Our proposal comprises the need for group management, traffic isolation, multi-hop route discovery protocol. We evaluate our protocol in a VLC environment, following a close indoor VLC. Our results evidence that multicast protocol over visible light communication can handle three more network flows than a simple unicast under a negligible overhead to maintain the multicast characteristics.